Effects of Mongolian Medicine Sengdeng-4 in Rabbit Knee Osteoarthritis Model (Central Asian Journal of Medical Sciences, 2023)
Objectives: Seng ldeng-4(SD-4) has a long history of use in Mongolian medical clinics for the treatment for rheumatic disorders. The objective of this study was to investigate the therapeutic effect and mechanism of SD-4 on rabbits with knee osteoarthritis induced by Hulth’s method.Methods: SD-4 (0.428and 0.857g·kg-1) or Zhuangguguanjie pill (0.514g·kg-1) were orally administered in rabbits for four weeks after the induction of knee osteoarthritis using Hulth’s method. Inflammation factors (TNF-α, IL-1β, and NO) and histopathological lesions in the knee joint were examined by ELISA and HE is staining. The expression of type II collagen mRNA in the articular cartilage was detected using real-time qPCR.Results: SD-4 ameliorated the articular lesion damage caused by Hulth’s method in rabbits and reduced the serum levels of inflammatory cytokines TNF-α, IL-1β, and NO. The qPCR results showed that the mRNA expression of type II collagen (COL2) and miRNA-140 gene in the model group was significantly lower than that in the control group (P